Investigation of the relationship between physical activity level and meaning in life of university students - Büşra Süngü; Ayşegül Demir Sarıipek (Physical Education of Students, 2023)
Background and Study Aim. In this study, it was aimed to examine the relationship between physical activity level and meaning of life in university students and to reveal possible differences according to demographic characteristics.